2022
DOI: 10.1097/in9.0000000000000004
|View full text |Cite
|
Sign up to set email alerts
|

Sex bias in systemic lupus erythematosus: a molecular insight

Abstract: Acknowledging sex differences in immune response is particularly important when we consider the differences between men and women in the incidence of disease. For example, over 80% of autoimmune disease occurs in women, whereas men have a higher incidence of solid tumors compared to women. In general women have stronger innate and adaptive immune responses than men, explaining their ability to clear viral and bacterial infections faster, but also contributing to their increased susceptibility to autoimmune dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 105 publications
0
7
0
5
Order By: Relevance
“…There is growing evidence that sex affects the pathophysiology, incidence, prevalence, development, and response to therapy in many diseases. In SLE, 90% of all diagnoses are in women [ 42 ], who are most commonly affected by clinical flares between the ages of 15 years and 44 years, or during childbearing years. Due to this disproportionality between sexes, this study aims to have a women:men ratio of 9:1, in keeping with SLE prevalence between sexes.…”
Section: Methodsmentioning
confidence: 99%
“…There is growing evidence that sex affects the pathophysiology, incidence, prevalence, development, and response to therapy in many diseases. In SLE, 90% of all diagnoses are in women [ 42 ], who are most commonly affected by clinical flares between the ages of 15 years and 44 years, or during childbearing years. Due to this disproportionality between sexes, this study aims to have a women:men ratio of 9:1, in keeping with SLE prevalence between sexes.…”
Section: Methodsmentioning
confidence: 99%
“…SLE is linked to several predisposing factors, like monogenic ( 20 23 ) and polygenic ( 24 , 25 , 131 , 132 ) abnormalities or combinations, sex/gender ( 133 ), and environmental factors ( 134 136 ). Autoimmunity is in this context not a predisposing factor but a disease-modifying factor.…”
Section: Controversies In Sle Research: Three Central But Unresolved ...mentioning
confidence: 99%
“…In this regard, it is known that the clinical manifestation of the disease typically appears after puberty, affecting women between the ages of 20 to 50, a period during which levels of estradiol and progesterone significantly rise ( 59 ). The strongest evidence supporting the role of female sex hormones in SLE comes from the observation that patients with SLE experience disease exacerbation during the premenstrual period and in pregnancy ( 35 , 59 ). Interestingly, a case report demonstrated that administering cross-gender hormones to a transgender female resulted in lupus nephritis, and the withdrawal of estradiol supplementation upon admission prevented the worsening of symptoms.…”
Section: The Impact Of Female Sex Hormones On B Cell Activation In Pa...mentioning
confidence: 99%
“…Animal studies also provide support for the role of estrogen in SLE. Ovariectomized lupus-prone mice showed ameliorated disease, while estrogen supplementation in castrated male mice worsened the symptoms [reviewed in ( 35 )]. Moreover, targeted deletion of ERα specifically in B cells has been shown to reduce the production of pathogenic autoantibodies and the development of nephritis in lupus-prone mice ( 61 ).…”
Section: The Impact Of Female Sex Hormones On B Cell Activation In Pa...mentioning
confidence: 99%
See 1 more Smart Citation